Ethnobotanical use of Morinda citrifolia: a literature review (Research, Society and Development, 2021)
Plant biodiversity has long been used by people for different purposes. In this sense, ethnobotany studies the practices related to plants carried out by different social groups, analyzing people-plant interactions. Among this biodiversity, Morinda citrifolia L. stands out, generally native to the tropical region, and popularly known as noni. This fruit has broad medicinal potential due to its antioxidant, dyslipidemic, hypotensive, healing, and antimicrobial properties, among others. Therefore, the objective of this research was to identify the prevalence of the use of Morinda citrifolia, in addition to demonstrating works with plant-related intoxications. Therefore, a systematic literature review was performed based on a search in the Scielo database, using the descriptor "Morinda citrifolia", finding a total of 17 studies published from 2016 to 2021. After reading the title and abstract, 12 articles were selected for having greater relevance and affinity with the topic under study. The inclusion criteria used were productions in the public domain that dealt with the proposed theme, works written in several languages ​​, and productions available in full, thus excluding documents that did not meet the aforementioned criteria. Literature analysis allowed us to identify the main uses of noni in the ethnobotanical aspect and its properties.